The contribution of phonological awareness and naming speed to reading vowelized and unvowelized texts in Arabic - Jabbour, Maysa; Ibrahim, Raphiq; Shany, Michal (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The aim of this study is to assess the contribution of and phonological awareness and naming speed abilities to reading in the Arabic language. For this purpose, 117 third and fifth grade Arabic-speaking children with intact verbal abilities were given measures of phonological awareness and naming speed, as well as reading measures of vowelized and unvowelized texts. The results revealed a modest correlation between phonological awareness and naming speed (NS) measures. Also, as predicted, a significant relationship was found between phonological awareness measures and reading accuracy; and between naming speed measures and fluency. Following, Hierarchal regression analyses revealed that, phonological awareness measures contributed significantly to variance in reading accuracy, and naming speed measures contributed a unique variance in reading fluency. Further analysis revealed that naming speed measures explain more variance in fluency and explained more variance in third grade than in fifth grade while phonological awareness measures explained more variance in fifth grade than in third grade. These results reveal that both abilities are key components in reading acquisition in Arabic, and that their relative contribution to reading not only depends on the orthographic transparency, but to other features as well.